Aetiology of acute febrile illness in children in a high malaria transmission area in West Africa. (April 2021) - Kaboré, B.; Post, A.; Lompo, P.; Bognini, J.D.; Diallo, S.; Kam, B.T.D.; Rahamat-Langendoen, J.; Wertheim, H.F.L.; van Opzeeland, F.; Langereis, J.D.; de Jonge, M.I.; Tinto, H.; et al.
Abstract: Objectives: Areas with declining malaria transmission in sub-Saharan Africa have recently witnessed important changes in the aetiology of childhood acute febrile illness (AFI). We describe the aetiology of AFI in a high malaria transmission area in rural Burkina Faso. Methods: In a prospective hospital-based diagnostic study, children aged 3 months to 15 years with AFI were recruited and assessed using a systematic diagnostic protocol, including blood cultures, whole blood PCR on a selection of bacterial pathogens, malaria diagnostics and a multiplex PCR on nasopharyngeal swabs targeting 21 viral and 4 bacterial respiratory pathogens. Results: A total of 589 children with AFI were enrolled from whom an infectious disease was considered in 575 cases. Acute respiratory tract infections, malaria and invasive bacterial infections (IBI) accounted for 179 (31.1%), 175 (30.4%) and 75 (13%) of AFI cases respectively; 16 (21.3%) of IBI cases also had malarial parasitaemia. A viral pathogen was demonstrated from the nasopharynx in 157 children (90.7%) with respiratory tract symptoms. Of all children with viral respiratory tract infections, 154 (92.4% received antibiotics, whereas no antibiotic was provided in 13 (17%) of IBI cases. Conclusions: Viral respiratory infections are a common cause of childhood AFI in high malaria transmission areas, next to malaria and IBI. These findings highlight the importance of interventions to improve targeted treatment with antimicrobials. Most patients with viral infections received antibiotics unnecessarily, while a considerable number with IBI did not receive antibiotics.